Konsep Kafa’ah Dalam Hukum Islam Urgensinya terhadap Keutuhan Rumah Tangga Sakinah Menurut Pandangan Wahbah Az-Zuhaili - Sahrun Anas; Sutisna sutisna; Hambari Hambari (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Kafaah in marriage is one of the factors that encourage the creation of happiness and more guarantees women's safety from husband and wife failure and more guarantees women's safety from failure or household turmoil. Based on the research results, first Jumhur ulama' explained that the concept of kafa'ah is not evaluated in terms of religion alone, but in Islamic Law, kafa'ah is measured from religious matters. The Compilation of Islamic Law (KHI) in determining the kafa'ah of marriage is more judgmental in terms of religion. Prevention of marriage can be done in certain matters that are discussed through KHI Article 60 Paragraph, second, that is prevention of marriage can be done if the prospective husband or prospective wife does not meet the requirements of marriage according to the law and Islamic law, because one of the content of the conditions of marriage is both couples are said to be valid when done in accordance with the laws of their respective religions. Third, the concept of kafa'ah of Wahbah Az-Zuhaili's view is in line with Imam Malik's opinion, which considers equality only in religion and conditions. The meaning of this condition is to be safe from the shame that makes a woman choose a candidate when she wants to get married. Wahbah Az-Zuhaili analyzed it in accordance with daily life in the community, 3) things that can affect the occurrence of harmony in the household, namely between husband and wife having compatibility. Harmony and happiness in a household is determined by the harmony of the couple. Keywords: Kafa'ah, Islamic Law, Urgency, Household Integrity, Wahbah Az-Zuhaili